A.1 CSF Findings in Early Active Autoimmune Encephalitis. (November 2021) - Hébert, J; Gros, P; Lapointe, S; Amtashar, FS; Steriade, C; Wennberg, RA; Day, GS; Tang-Wai, DF
Abstract : Background: Treatment decisions for patients with autoimmune encephalitis (AE) frequently need to be made before results from autoantibody testing are available, as early treatment is associated with better outcomes. Cerebrospinal fluids (CSF) white blood cell (WBC) count and protein concentration measured early on in the disease process is often used, in combination with other clinical factors, to evaluate the likelihood that a patient has AE. Methods: CSF characteristics (WBC count, protein concentration, and oligoclonal banding) measured in a first AE presentation, prior to results of autoantibodies being available, were retrospectively analyzed at two tertiary care centers. Results: Ninety-five patients were included in the study. CSF WBC counts and protein levels were within normal limits for 27% (CI95%: 19–37) of patients with AE. When results of oligoclonal banding were added, 14% (CI95%: 6–16) of patients had "normal" CSF. The median CSF white blood cell count was 8 cells/mm3 (range: 0–544) and the median CSF protein concentration was 0.42 g/L (range: 0.15–3.92). Conclusions: A substantial proportion of patients with early active AE had a CSF WBC count or protein concentration within the normal. Inclusion of CSF oligoclonal banding may help identify a higher proportion of patients with an inflammatory CSF profile early in the disease process.